2019
DOI: 10.1111/jfpp.13889
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, antioxidant, and sensorial impacts of oregano and rosemary essential oils over broccoli florets

Abstract: Combination of oregano and rosemary essential oils (EOs) was proposed to obtain a better antimicrobial and antioxidant effect on fresh‐cut broccoli compared to the use of individual oils. In in vitro assays, EOs combinations (oregano + rosemary) were more effective to inhibit the growth of Escherichia coli O157:H7, Salmonella Choleraesuis, Listeria monocytogenes, and Staphylococcus aureus compared to individual EOs doses. Oregano EO showed a higher antioxidant power compared to rosemary tested by DPPH and TEAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…Additionally, it has been reported that the combination of EOs showed a synergistic effect on the antioxidant activities of EOs [ 34 , 198 ]. Misharina and Samusenko [ 199 ] determined the antioxidant properties of several EOs either as single or in combination ( Citrus limon L. (lemon), Citrus paradisi L. (pink grapefruit), Coriandrum sativum L. (coriander), and Caryophyllus aromaticus L. (clove buds)).…”
Section: Antioxidant Activities Of Essential Oilsmentioning
confidence: 99%
“…Additionally, it has been reported that the combination of EOs showed a synergistic effect on the antioxidant activities of EOs [ 34 , 198 ]. Misharina and Samusenko [ 199 ] determined the antioxidant properties of several EOs either as single or in combination ( Citrus limon L. (lemon), Citrus paradisi L. (pink grapefruit), Coriandrum sativum L. (coriander), and Caryophyllus aromaticus L. (clove buds)).…”
Section: Antioxidant Activities Of Essential Oilsmentioning
confidence: 99%
“…On the other hand, extrinsic factors and described by ecological and environmental aspects such as attitude, soil composition, climate and light, all these factors can drastically affect the chemical composition of essential oils (Stahl-Biskup, 2002). Thus, these variations are of distinct important when studying the biological activity, such as, anti-oxidant capacity of essential oils as the degree of activity has to be related to its chemical composition (Panizzi et al, 1993;Lahlou and Berrada, 2003;Alvarez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Alvarez et al. (2019) demonstrated the inhibition of the coliforms’ growth on fresh‐cut broccoli by a combination of oregano and rosemary essential oil (Alvarez et al, 2019). Another study on the refrigerated chicken meat covered with cellulose acetate film and REO reported that the coliform growth in the film containing 50% REO was significantly controlled and reduced compared to the control sample during the storage period, while the films that contained 20% essential oil did not demonstrate significant antimicrobial effect (Melo et al., 2012).…”
Section: Resultsmentioning
confidence: 99%